THE IMPORTANCE OF EQUATING PARENT’S PERCEPTIONS WITH CHILDREN’S HOBBY IN USING ANDROID-BASED APPLICATIONS AS A LEARNING MEDIA - Prameswari, Nadia; Suharto, Mohamad; Prabowo, Tjahjo (PEOPLE: International Journal of Social Sciences, 2017)
The advancement of technology makes the emergence of various Android-based applications ranging from games to learning media. These applications have become part of the daily lives of children, which cannot be prevented, and it goes naturally. Therefore, children aged 7-8 years need special attention and assistance by parents so that type of children’s favorite application will be known. This research used qualitative method.To collect data, samples were selected using random sampling. This research aims to (1) review the learning media, namely Android-based applications, which are favored by children; and (2) know parents’ perception of the learning media favored by children. The results showed that the importance of equating parent’s perception with children’s hobby, due to the children’s interest to the application as a new media in learning, can provide learning motivation for children. The importance of equating perceptions between parents and children, due to the children’s interest to the application as a new media in learning, can provide motivation and self-development for children.This research is expected to be developed to the stage of researching the education administrator policy toward the correlation with the government policy and the ongoing curriculum.